Anomalous > 2000‐Year‐Old Surface Ocean Radiocarbon Age as Evidence for Deglacial Geologic Carbon Release. Issue 23 (11th December 2019) - Rafter, Patrick A.; Carriquiry, José D.; Herguera, Juan‐Carlos; Hain, Mathis P.; Solomon, Evan A.; Southon, John R.
Abstract: Geologic carbon from seafloor volcanism may influence late Pleistocene glacial terminations by increasing the global inventory of the greenhouse gas CO2 . However, the evidence for geologic carbon flux associated with deep sea volcanism has been, so far, equivocal. Here, we construct a regional, glacial‐deglacial carbon budget of the volcanically active Gulf of California using microfossil 14 C measurements and find results consistent with an increased addition of geologic carbon related to local seafloor volcanism during the deglaciation. Our estimates point to enhanced geologic carbon flux both before and during the last deglaciation that generally occur alongside carbonate preservation. This leads us to suggest that the carbon was added in the form of partially neutralized, 14 C‐free bicarbonate associated with known Gulf sedimentary processes—a carbon source that would have a minimal effect on atmospheric CO2 . Plain Language Summary: We account for the carbon entering and leaving the waters of the Gulf of California since the last ice age. Our results argue for increased supply of geologic carbon alongside enhanced volcanic activity after the last ice age. We argue that this delivery of geologic carbon to Gulf seawater was in the form of bicarbonate, not CO2, which would have a minimal impact on seawater acidity and is consistent with global sedimentary records. Key Points: Recent work suggests increased carbon flux from seafloor volcanism during deglaciation We identify increased carbon flux with a unique application of microfossil radiocarbon content in the volcanically active Gulf of California This geologic carbon may arrive via sediment pyrolysis and anaerobic oxidation of methane, with a minimal influence on seawater pH